The Polycyclic Polyprenylated Acylphloroglucinol Antibiotic PPAP 23 Targets the Membrane and Iron Metabolism in Staphylococcus aureus - Wang, Huanhuan; Kraus, Frank; Popella, Peter; Baykal, Aslihan; Guttroff, Claudia; François, Patrice; Sass, Peter; Plietker, Bernd; Götz, Friedrich (Frontiers in Microbiology, 2019)
Recently, a series of endo-type B polycyclic polyprenylated acylphloroglucinols (PPAP) derivatives with high antimicrobial activities were chemically synthesized. One of the derivatives, PPAP 23, which showed high antimicrobial activity and low cytotoxicity, was chosen for further investigation of its bactericidal profiles and mode of action. PPAP 23 showed a better efficacy in killing methicillin resistant S. aureus (MRSA) and decreasing the metabolic activity of 5-day-old biofilm cells than vancomycin. Moreover, S. aureus did not appear to develop resistance against PPAP 23. The antimicrobial mechanism of PPAP 23 was investigated by RNA-seq combined with phenotypic and biochemical approaches. RNA-seq suggested that PPAP 23 signaled iron overload to the bacterial cells because genes involved in iron transport were downregulated and iron storage gene was upregulated by PPAP 23. PPAP 23 affected the membrane integrity but did not induce pore formation; it inhibited bacterial respiration. PPAP 23 preferentially inhibited Fe-S cluster enzymes; it has a mild iron chelating activity and supplementation of exogenous iron attenuated its antimicrobial activity. PPAP 23 was more effective in inhibiting the growth of S. aureus under iron-restricted condition. The crystal structure of a benzylated analogue of PPAP 23 showed a highly defined octahedral coordination of three PPAP ligands around a Fe (3+) core. This suggests that PPAPs are generally capable of iron chelation and are able to form defined stable complexes. PPAP 23 was found to induce reactive oxygen species (ROS) and oxidative stress. Fluorescence microscopic analysis showed that PPAP 23 caused an enlargement of the bacterial cells, perturbed the membrane, and dislocated the nucleoid. Taken together, we postulate that PPAP 23 interacts with the cytoplasmic membrane with its hydrophobic pocket and interferes with the iron metabolism to exert its antimicrobial activity in Staphylococcus aureus.